2010
DOI: 10.1038/nmat2851
|View full text |Cite
|
Sign up to set email alerts
|

Measuring fundamental properties in operating solid oxide electrochemical cells by using in situ X-ray photoelectron spectroscopy

Abstract: Photoelectron spectroscopic measurements have the potential to provide detailed mechanistic insight by resolving chemical states, electrochemically active regions and local potentials or potential losses in operating solid oxide electrochemical cells (SOCs), such as fuel cells. However, high-vacuum requirements have limited X-ray photoelectron spectroscopy (XPS) analysis of electrochemical cells to ex situ investigations. Using a combination of ambient-pressure XPS and CeO(2-x)/YSZ/Pt single-chamber cells, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
321
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 272 publications
(334 citation statements)
references
References 39 publications
11
321
1
1
Order By: Relevance
“…18,31 The shift in apparent binding energy of an electron under an applied bias is a direct measure of the local surface potential compared to the open circuit voltage (OCV), enabling correlation of surface chemistry with local potentials. [32][33][34] The combination of these features makes AP-XPS an excellent tool for studying electrochemical reactions at the catalyst surface.…”
Section: Ambient Pressure X-ray Photoelectron Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…18,31 The shift in apparent binding energy of an electron under an applied bias is a direct measure of the local surface potential compared to the open circuit voltage (OCV), enabling correlation of surface chemistry with local potentials. [32][33][34] The combination of these features makes AP-XPS an excellent tool for studying electrochemical reactions at the catalyst surface.…”
Section: Ambient Pressure X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…The persistence of the Ce 3+ /Ce 4+ shifts within this active region suggests that the surface reaction kinetics and lateral electron transport on the thin ceria electrodes are co-limiting processes. 32 Building upon this work, the relation of Ce redox to oxygen speciation was recently investigated, in order to "observe" charge separation at an SOEC gas−solid interface and monitor changes in chemical intermediates involved in the electrochemical process. Within the electrochemically active region of the SOEC, a separation of local surface potentials of adsorbed OH − and incorporated O 2− ions due to a build-up of surface Ce 3+ was observed, proposed to be a result of rate-limiting charge transfer processes.…”
Section: Insights From Operando Electrochemical Measurementsmentioning
confidence: 99%
“…There is only a slight shift in the charged components corresponding to the difference in interdigit spacing. For C 60 , in which electron mobility is significantly greater than hole mobility, the charged gold components are shifted much closer to the grounded Au 4f emission. Alternatively, for TiOPc, where hole mobility is highest, the shift of the charged Au 4f emission is less than was observed for C 60 .…”
Section: Tiopc and C 60 On Gold Idesmentioning
confidence: 93%
“…A 10 MHz quartz crystal microbalance (QCM) with a frequency counter (Agilent 53181A) and a timing circuit (International Crystal Manufacturing 35360) was used to monitor the rate of deposition. Deposition rates were approximately 3 Hz/s corresponding to temperatures of approximately 450 o C and 370 o C, for C 60 and TiOPc, respectively. 13,6-N-sulfinylacetamidopentacene (precursor), obtained from Aldrich, was dissolved in chloroform.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Cai et al used angle resolved X-ray photoelectron spectroscopy (ARXPS) to study the reversible reduction of cobalt in strained La 0.8 Sr 0.2 CoO 3 , a phenomenon associated with increased surface vacancy concentrations, at high temperature in vacuum [45]. Zhang et al further performed ambient in situ synchrotron XPS to characterize CeO 2−δ /YSZ/Pt cells and establish the relation between the kinetic energy shift of the core-level spectra and the local surface potential and local overpotentials of the cell components [46]. Mutoro et al combined oxygen-atmosphere with external electrochemical potential and found reversible compositional changes in LSC thin films at elevated temperature [47].…”
Section: Chemical Structural and Morphologicalmentioning
confidence: 99%